Performance variables and nutritional status analysis from Moroccan professional and adolescent football players during the competition period: a descriptive study - Oukheda, M.; Lebrazi, H.; Derouiche, A.; Kettani, A.; Saile, R.; Taki, H. (Frontiers in Sports and Active Living, 2024)
Introduction: Nutrition plays an integral role in optimizing football players` performance during training sessions and matches and maintaining their overall health throughout the season. This study aimed to evaluate how well the dietary practices of professional and adolescent football players in Morocco during the competitive period met international macronutrient recommendations, and to explore the relationship between their nutritional status and aerobic performance, as measured by the Yo-Yo IRL1 test.